2016
DOI: 10.1159/000446067
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect Tissue-Engineered Skeletal Muscle Function and Physiology

Abstract: Tissue-engineered skeletal muscle has the promise to be a tool for studying physiology, screening muscle-active drugs, and clinical replacement of damaged muscle. To maximize the potential benefits of engineered muscle, it is important to understand the factors required for tissue formation and how these affect muscle function. In this review, we evaluate how biomaterials, cell source, media components, and bioreactor interventions impact muscle function and phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 83 publications
0
27
0
Order By: Relevance
“…These results suggest that the crosslinking density of hydrogels depends on the composite material, UV dosage, and type of photoinitiator. Furthermore, as previously indicated, the mechanical properties of hydrogels strongly impact muscle function and phenotype . Therefore, it is of great interest to make hydrogels mimicking the biological scaffolds with tunable mechanical properties.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…These results suggest that the crosslinking density of hydrogels depends on the composite material, UV dosage, and type of photoinitiator. Furthermore, as previously indicated, the mechanical properties of hydrogels strongly impact muscle function and phenotype . Therefore, it is of great interest to make hydrogels mimicking the biological scaffolds with tunable mechanical properties.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, as previously indicated, the mechanical properties of hydrogels strongly impact muscle function and phenotype. [39,[42][43][44]52] Therefore, it is of great interest to make hydrogels mimicking the biological scaffolds with tunable mechanical properties. It is possible to increase the mechanical properties of hydrogels to increase the hydrogel concentration, the UV dosage, or the photoinitiator.…”
Section: Composite Hydrogels With Tunable Mechanical Propertiesmentioning
confidence: 99%
“…[9,116,126,141,151] Notably, even when similar tissue-engineering methodologies are used, specific forces vary widely depending on the source of myogenic cells, increasing from C2C12, to human, to adult rat, to neonatal rat cells. [152] Engineered muscles also retain the contractile and metabolic phenotype specific to the muscle from which cells are isolated demonstrating that epigenetic differences in vivo are retained in vitro. [153,154] The ability to engineer muscle with a particular fiber type is important for studying certain diseases such as Pompe disease, Duchenne muscular dystrophy (DMD), and sarcopenia that preferentially target fast muscle fibers.…”
Section: Methods To Improve Engineered Muscle Functionmentioning
confidence: 99%
“…Stiffness gradients of hydrogel or polyacrylamide and stretch bioreactors are also used to study the effects of mechanotransduction, as shown for MSC migration and fate; and adipogenesis was significantly upregulated by gels that mimicked the native stiffness of adipose tissue (2 kPa) . For contractile tissues such as skeletal muscles, mechanical forces and structural strength are of particular importance (as well as electrical stimulation) and there is much interest in such bioengineered muscle constructs …”
Section: Part A: Major Advances In Tissue Culture For Bioengineering:mentioning
confidence: 99%